Enhancing Learning Activeness of Students through Project-Based Learning - Tri Fitriani; Andri Wahyono; Ikbal Barlian (Jurnal Pendidikan Ekonomi, 2024)
Students’ learning activeness is the most crucial element as its impact on educational success while implementing project-based learning seems relevant in economics learning. Therefore, this study aims to investigate the impact of the project-based learning model on students learning activeness. This study involved classroom action research which conducted at senior high school 5 Palembang in Indonesia. To gather the data, this present study incorporated observation sheets, which were further analyzed using MILES procedures, which consist of planning, action, observation, and reflection, respectively. The finding of this study indicates that the students learning activeness in the pre-cycle were in a low category (49%), and it reached 56% in the first cycle to reach 56% and 68% in the second cycle. Compared to the third cycle, it experienced a dramatic change to reach 80% or a high category. Therefore, there is a need for teachers and schools to make innovations and variations in the classroom teaching-learning process to enhance activeness and meaningful learning.